Social aspects of the development of family taxation in the Russian Federation - T. V. Zvereva (Цифровая социология)
The priority direction of tax policy of the Russian Federation (hereinafter referred to as RF, Russia) is its focus on building a social state in the country and developing mechanisms for implementation of effective social policy. This article explores possibilities of considering а taxpayer’s family status in determination of tax burden on personal income tax. The purpose of the article is to conduct the author’s research of the results of applying existing approaches and the potential and expe diency of introducing family taxation in Russia with consideration to foreign experience and its adaptation to modern Russian realities. With the help of the method of system analysis, the author uses sociological and economic approaches to study the family as a social institution and economic association of close relatives, and regards implementation of the principle of fairness of taxation from the point of view of a socially-oriented approach. Based on the research of the foreign experience and provisions of the Russian tax legislation, the expediency of applying in Russia income taxation of family as a consolidated group of taxpayers with joint liability for the fulfilment of tax obligations is substantiated. The author’s definition of the family as an object of tax relations is given. The order of taxation of the aggregate family income in the calculation of personal income tax is proposed. The mechanism of using family taxation is described, the introduction of which meets the realisation of priority goals of the tax policy of Russia, development of the social state. The conducted analysis has shown that in the tax legislation, when providing privileges, the family status of the payer is considered. The development of this approach will further create conditions for strengthening the family as a source of morality, patriotism, culture of the younger generation.